Enhancing learning activities and problem-solving skills of students with disabilities through collaborative problem-solving models - Pamuji, Pamuji; Khotimah, Nurul; Arianto, Fajar; Sartinah, Endang Pudjiastuti; Yanuartuti, Setyo (Edelweiss Applied Science and Technology, 2026)
This study aims to investigate the effectiveness of the Collaborative Problem Solving (CPS) model in enhancing learning activities and problem-solving skills among students with disabilities in special schools. A quantitative approach was employed, utilizing a quasi-experimental, nonequivalent pretest–posttest control group design. The sample consisted of 130 students, divided into an experimental group (n = 65), which received CPS-based instruction, and a control group (n = 65), which received conventional teaching methods. Data collection involved pretests and posttests to assess problem-solving skills, complemented by systematic observations of learning activities. Pretest results indicated no significant difference between the experimental and control groups (p = 0.648), demonstrating comparable initial abilities. Posttest results revealed that the experimental group achieved significantly higher scores (M = 81.54, SD = 6.05) compared to the control group (M = 75.92, SD = 7.65), with a statistically significant difference (t = 4.641, p = 0.000). Observational data further indicated increased student engagement, collaboration, and active participation within the CPS group. The findings suggest that the CPS model is effective in improving learning activities and problem-solving skills among students with disabilities. Implementing CPS as an instructional strategy in special education settings can foster active learning, enhance collaboration, and lead to improved cognitive outcomes. These results support the integration of CPS into teaching practices to promote more inclusive and effective educational environments for students with diverse learning needs.